2019
DOI: 10.18502/sjms.v14i4.5909
|View full text |Cite
|
Sign up to set email alerts
|

The Irrational Use of Antibiotics Among Doctors, Pharmacists and the Public in River Nile State, Sudan

Abstract: Background: Inappropriate antibiotic prescription, dispensing and self-medication are alarmingly high worldwide. The problem is more so in developing countries, including Sudan, where resistance to life-saving drugs is emerging. Objective: to assess the prevalence of irrational use of antibiotics among doctors, pharmacists and the public in River Nile State (RNS), Sudan. Methodology: a descriptive cross-sectional study was conducted, in March 2014 through April 2014. The study population was 278 individuals, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Prevalence of irrational use of antibiotics in different Prevalence of irrational use of antibiotics in different levels of the community levels of the community Despite the few numbers of data published in Sudan, the results shown were surprising and indicate an upcoming crisis in Sudan. However, the irrational use of antibiotics is practiced by doctors, pharmacists, and community members as shown in the study done by (Sara H Oleim et al, 2019) in River Nile State (RNS) in Sudan (2). Accordingly, patterns of antibiotics misuse in this study showed that 92.0% of doctors are prescribing antibiotics without culture and sensitivity tests while less than 10.0% depend on culture and sensitivity tests.…”
Section: Discussion Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Prevalence of irrational use of antibiotics in different Prevalence of irrational use of antibiotics in different levels of the community levels of the community Despite the few numbers of data published in Sudan, the results shown were surprising and indicate an upcoming crisis in Sudan. However, the irrational use of antibiotics is practiced by doctors, pharmacists, and community members as shown in the study done by (Sara H Oleim et al, 2019) in River Nile State (RNS) in Sudan (2). Accordingly, patterns of antibiotics misuse in this study showed that 92.0% of doctors are prescribing antibiotics without culture and sensitivity tests while less than 10.0% depend on culture and sensitivity tests.…”
Section: Discussion Discussionmentioning
confidence: 46%
“…At the time of writing, there were few published papers conducted on irrational use of antibiotics and antimicrobial resistance in Sudan (2). Nonetheless, the absence of an antibiotic stewardship program that is applied and activated in Sudan's healthcare system is an alarming concern in regards to the issue of antibiotics resistance.…”
Section: Discussion Discussionmentioning
confidence: 99%
See 3 more Smart Citations